ANALISIS NILAI-NILAI PENDIDIKAN TAUHID: Study Kitab ‘‘Aqidah al-‘Awam Karya Sayyid Ahmad Al-Marzuqi: Study Kitab ‘Aqidah al-‘Awam Karya Sayyid Ahmad Al-Marzuqi - Nur Qomari (Jurnal Penelitian Ilmiah INTAJ, 2022)
This study aims to determine how tauhid education according to Sayyid Ahmad Al-Marzuqi in the book ‘Aqidah al-‘Awam. In addition, they also know the significance of monotheism education in everyday life. The type of research used in this study is qualitative using a library approach. The primary data source is the ‘Aqidah al-‘Awam book, the secondary source is the translation and the tertiary source is books and other books that are relevant and relevant to the research. The findings of this study indicate that the book ‘Aqidah al-‘Awam by Sayyid Ahmad Al-Marzuqi is still relevant in education from the past to education today. The value of tauhid education is faith education where faith itself consists of faith in Allah, in angels, in books, in the Apostles, in the Last Day, and faith in qadla and qadr. The significance of tauhid education in everyday life from the attributes of Allah SWT is the door to success in life in the world and the hereafter, and as a reference in creating morality, besides that by implementing the attributes of Allah in everyday life can facilitate social relations. both in religious matters or between communities, as well as according to the syari’ah and norms that apply in the community itself.